Produção de petróleo e desenvolvimento a contribuição dos royalties na dinâmica regional do território Açu / Mossoró - Góis, Breno Vinícius de (Universidade Federal Rural do Semi-Árido, 2014)
The exploration and production of oil in Brazil evolved forcefully since the year 1997, the year in which there was a relaxation of the oil monopoly, which made possible that such activity was the object of granting strangers to Public Administration . Such flexibility caused an enormous growth in the oil sector, since there were several interested in prospecting for oil in national soil. It happens that in return, the dealer had to pay the state a monthly amount calculated upon a percentage (between 5% and 10%) of the production of oil or natural gas, called royalty. Allied to this, installation of the exploration and production of oil in a particular local industry carries significant social and environmental damage, such as depletion of non-renewable resource, deforestation for infrastructure, territorial consolidation. Thus, the research problem of this study arises: the use of the values passed as royalties should be linked to the negative impacts that cause the production of oil, such as repairing the environment or future generations by compensating resource depletion ? In this sense, this paper analyzes the trends of the contribution of funds from the Royalties in the Municipalities Planning Acu / Mossley brought social development for such localities. For this, we will review progress on the Human Development Index - HDI in these municipalities before and after the significant contribution of royalties, and perform a detailed study on the town of Mossoró / RN, which passes through a cooling of the oil industry
Oil production and development - the contribution of royalties on dynamic regional of the planning Açu / Mossoró
Keywords: Social development; Oil exploration; HDI; Social impacts; Desenvolvimento social; Exploração de petróleo; IDH; Impactos Sociais; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE